Expression Profiles of Phosphoenolpyruvate Carboxylase and Phosphoenolpyruvate Carboxylase Kinase Genes in Phalaenopsis, Implications for Regulating the Performance of Crassulacean Acid Metabolism - Ping, Chia-Yun; Chen, Fure-Chyi; Cheng, Teen-Chi; Lin, Huey-Ling; Lin, Tzong-Shyan; Yang, Wen-Ju; Lee, Yung-I (Frontiers in Plant Science, 2018)
Phalaenopsis is one of the most important potted plants in the ornamental market of the world. Previous reports implied that crassulacean acid metabolism (CAM) orchids at their young seedling stages might perform C3 or weak CAM photosynthetic pathways, but the detailed molecular evidence is still lacking. In this study, we used a key species in white phalaenopsis breeding, Phalaenopsis aphrodite subsp. formosana, to study the ontogenetical changes of CAM performance in Phalaenopsis. Based on the investigations of rhythms of day/night CO2 exchange, malate contents and PEPC activities, it is suggested that a progressive shift from C3 to CAM occurred as the protocorms differentiated the first leaf. To understand the role of PEPC kinase in relation to its target PEPC in CAM performance in Phalaenopsis, the expression profiles of the genes encoding PEPC and PEPC kinase were measured in different developmental stages. In Phalaenopsis, two PPC isogenes were constitutively expressed over a 24-hr cycle similar to the housekeeping genes in all stages, whereas the significant day/night difference in PaPPCK expression corresponds to the day/night fluctuations in PEPC activity and malate level. These results suggest that the PaPPCK gene product is most likely involved in regulation of CAM performance in different developmental stages of Phalaenopsis seedlings.